2022
DOI: 10.1155/2022/9381881
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Limb Extension of Referred Trigeminal Facial Pain due to Greater Occipital Nerve Entrapment: A Case Report

Abstract: We report a very rare case of referred pain associated with entrapment of the greater occipital nerve (GON) occurring not only in the ipsilateral hemiface but also in the ipsilateral limb. There is an extensive convergence of cutaneous, tooth pulp, visceral, neck, and muscle afferents onto nociceptive and nonnociceptive neurons in the trigeminal nucleus caudalis (medullary dorsal horn). In addition, nociceptive input from trigeminal, meningeal afferents projects into trigeminal nucleus caudalis and dorsal horn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Te pain location in the submandibular area of the current case, which was difcult to explain, coincided with subauricular and submandibular areas known to be pain distribution areas of GON entrapment [18][19][20][21][22][23][24]. In addition, it has been reported that referred pain of chronic GON entrapment might extend not only to trigeminal distribution but also the arms and legs [26].…”
Section: Case Reportsupporting
confidence: 56%
See 4 more Smart Citations
“…Te pain location in the submandibular area of the current case, which was difcult to explain, coincided with subauricular and submandibular areas known to be pain distribution areas of GON entrapment [18][19][20][21][22][23][24]. In addition, it has been reported that referred pain of chronic GON entrapment might extend not only to trigeminal distribution but also the arms and legs [26].…”
Section: Case Reportsupporting
confidence: 56%
“…Te author's GON decompression technique using an oblique, paramedian approach using a microscope has already been reported [20][21][22][23][24][25][26]. In brief, it is a distal approach that frst addresses the distal branch of the GON that has passed through the trapezial canal.…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations